Improving Oxygen Reduction Reaction ORR Fuel Cell Efficiency with Carbon Nano Onions - Steiger, Florian; Kaiser, Pascal; Assebban, M'hamed; Hirsch, Andreas; Abellan, Gonzalo; Echegoyen, Luis; Mayrhofer, Karl J. J.; Cherevko, Serhiy; Perez-Ojeda Rodriguez, Maria Eugenia; Lloret Segura, Vicente Josep (243rd ECS Meeting with the Eighteenth International Symposium on Solid Oxide Fuel Cells, 2023)
Hydrogen Fuel cell innovations are cutting-edge clean power solutions highly demanded nowadays. Since the oxygen reduction reaction (ORR) in fuel cells needs to be catalyzed heterogeneously, conductive substrates such as carbon materials are critical for the construction of electrocatalysts. Thus far, the research has been focused on commercially available carbon supports such as the well-known Vulcan, and the high-surface area Ketjenblack.[1] Thanks to the fast development of material science, other carbon supports such as graphite, graphene oxide, and carbon nanotubes have been also studied in a lesser extent, mainly due to their novelty and underdeveloped scale up syntheses.[2,3] This work focuses on utilizing a relatively new and, as of yet, largely unexplored carbon nanomaterial: carbon nano onions (CNOs). CNOs are spherical nanoparticles of about 5 nm diameter composed of concentrical multi-layered fullerenes, first discovered by Ugarte in 1992. CNOs exhibit outstanding properties such as low density, high thermal stability, and a graphitic multilayer morphology, which makes them excellent candidates for a wide variety of applications. Furthermore, the onion's large surface area and high conductivity make them particularly interesting as catalyst support for electrochemical applications as they have already been demonstrated to be a superior Pt support alternative thanks to a higher cycling stability compared to carbon black, since their particle size and morphology suppress catalyst agglomeration and avoid its ripening.[4] However, despite their excellent long-term stability, the few available studies using CNOs were performed using the rotatory disc electrode (RDE) method, reaching only modest performance in the mA / cm2 range. Thus, our work aims to further extend upon this research by measuring the ORR performance with a gas diffusion electrode (GDE), to reproduce realistic fuel cell conditions.[5] The catalyst layer, obtained by growing Pt nanoparticles on CNOs, is characterized by electrochemical measurements such as ORR polarization curves, electrochemical active surface area (ECSA) by the CO-stripping method, and O2-mass transport. The utilization of GDE cells allows for higher current densities and a realistic catalyst mass transport compared to the RDE method, thus better representing an applied ORR fuel cell test.[